Communicative potential of literary phraseology in the media - Zbinska , Anna (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article is devoted to stylistic functions of literary phraseology in media communication. The author opinion that the media sphere is a special type of verbalized language consciousness that commensurates with actual processes of language development is formulated and argued. Language markers, representative for the media, their origin, functional resource, effective forms of presentation, analysis of the ability to influence the semantic development of language and form the cultural field of modern mass consciousness are important issues for a linguist in such investigation objectivity. The emphasis is made on the fact that the active processes of development of modern information societies cause the transformation of language communication, in particular in the media, where the functional intentions of the literary word and phraseology are significant and effective. The functions of literary phraseology of biblical origin, author’s phraseology of Ukrainian writers in media communication are considered, primarily from the point of view of their transformation, ability to unite the text. Special attention is also focused on the intertextual possibilities of literary phraseology as the ability of intercultural semantic circles to outline the associative aesthetic and ethical potential of modern European culture. The author interprets the intentions of phraseological units as multivariate communicative units, characterized by semantic field, aptness, stability and the mentioned emotional, expressive potential, that collectively allows to perform a manipulative function and strengthen the influence on the recipient’s consciousness. The use of literary phraseology in the media, which is determined by the expressive potential of these language units, the conciseness of the form, the ability to symbolize, to combine humanistic ideas and intercultural ties of modern civilization, is elaborated. Emphasis is placed on the expediency and perspective of interpreting the possibilities of literary phraseology in the active communicative space of the media.